Mental health problems during COVID-19 pandemic among undergraduates in clinical compared to non-clinical programs - Sumaiyah Mat; Teoh, Jun Jie; Ding, Pei Xian; Muhammad Aiman Wafi Termizi; Muhammad Farhan Norhalim; Nawwal Atikah Badri; Ng, Xian Yu; Tan, Jia Xian; Nor Azlin Mohd Nordin; Normala Mesbah; Nor Azura Azmi; Asfarina Zanudin; et al. (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aimed to determine undergraduates’ mental health status, quality of life and burn-out status in clinical and non-clinical programs as well as its association during COVID-19 pandemic period. A cross sectional survey was carried out by distributing the questionnaire through online social media platforms such as WhatsApp, Facebook, and Twitter. Mental health, burn-out statuses and quality of life of the undergraduates were assessed using 21-item Depression Anxiety Stress Scale (DASS-21), Copenhagen Burnout Inventory and Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q-SF) respectively. A total of 308 respondents (111 from clinical, 197 from non-clinical programs), mean (SD) age=21.88(1.29) years participated in this cross-sectional online survey. The results revealed that undergraduates in the non-clinical programs are more likely to experience higher levels of depression, anxiety and stress, whichdemonstrated by higher median (IQR) scores in each component of DASS-21 (Non-clinical VS Clinical) [depression, 18 (10-28) VS 8 (2-20); anxiety, 16 (8-26) VS 10 (2-16), and stress, 20 (12-28) VS 12 (4-22)]. Similarly, higher burnout median score, 58.83 (48.83 - 75.00) was noted among undergraduates in non-clinical programs with a lower mean (SD) Q-LES- Q-SF score=58.75 (18.03). Undergraduates with good internet accessibility had higher quality of life scores [2.06(1.03-4.13)]. The association between lower mental health status, QoL and burn-out among non-clinical students remained significant even after adjustment for gender, household income, type of university (IPTA vs IPTS), race, and internet accessibility at university. Our findings suggest that undergraduates from clinical programs had better mental health status and quality of life when compared to their peers from non-clinical programs during COVID-19 pandemic period.